On the avifauna of the upper patía valley, southwestern colombia (1986)
The bird fauna of the isolated arid Andean valley of the upper río Patia, southwestern Colombia, resembles that of the Cauca Valley to the north.  The most prominent faunal element are widely distributed nonforest birds of the Tropical Zone which entered the Andean valleys of Colombia from the Caribbean lowlands to the north. The relations between the upper Patía fauna and the nonforest fauna of western Ecuador to the south are very restricted (e.g. Veniliornis callonotus). Montane species of the Upper Tropical Subtropical Zone that inhabit the upper Patía Valley include the antshrike Thamnophilus multistriatus, the nightingale-thrush Catharus aurantiirostris, the warbler Basileuterus culiciuorus and others.  Some of the Patía populations differ from conspecific Cauca Valley populations by paler plumage coloration reflecting the arid climate of the restricted mountain valley of the upper río Patía, especially those of Forpus conspicillatus and Catharus aurantiirostris. However, these differences together with the c1inal nature of the geographical variation do not warrant taxonomic recognition as separate subspecies.